Comparative efficiency and safety of potassium competitive acid blockers versus Lansoprazole in peptic ulcer: a systematic review and meta-analysis - Dong, Yongqi; Xu, Hongyan; Zhang, Zhihuan; Zhou, Zhihang; Zhang, Qiang (Frontiers in Pharmacology, 2024)
Background: Lansoprazole, a proton-pump inhibitor (PPI), is the primary therapy for peptic ulcers (PU). Potassium competitive acid blockers (P-CAB) offer an alternative for acid suppression. However, the efficacy and safety of P-CABs versus lansoprazole in the management of PU has not been evaluated. Methods: Five databases were searched for randomized clinical trials in English until 31 August 2023. Data extraction provided outcome counts for ulcer healing, recurrent NSAID-related ulcer, and adverse events. The pooled effect, presented as rate difference (RD), was stratified by ulcer location, follow-up time, and the types of P-CAB, along with their corresponding 95% confidence intervals (95% CI). Results: The pooled healing rates of peptic ulcers were 95.3% (1,100/1,154) and 95.0% (945/995) for P-CABs and lansoprazole, respectively (RD: 0.4%, 95% CI: −1.4%–2.3%). The lower bounds of the 95% CI fell within the predefined non-inferiority margin of −6%. In subgroup analyses base on ulcer location, and follow-up time also demonstrated non-inferiority. The drug-related treatment-emergent adverse events (TEAEs) did not differ significantly among groups (RR: 0.997, 95% CI: 0.949–1.046, p = 0.893). However, P-CAB treatment was associated with an increased risk of the serious adverse events compared to lansoprazole (RR: 1.325, 95% CI: 1.005–1.747, p = 0.046). Conclusion: P-CABs demonstrated non-inferiority to lansoprazole in the management of peptic ulcer. The safety and tolerability profile are comparable, with similar TEAEs rates. However, P-CABs appear to have a higher risk of serious adverse events. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=458361 Identifier: PROSPERO (No. CRD42023458361).